Regulation of hnRNP A1 Cellular Localization by Protein Kinases and its Biological Impact - Courteau, Lynn (Université d'Ottawa / University of Ottawa, 2015)
Human Rhinoviruses (HRVs) utilize Internal Ribosome Entry Sites (IRES) to drive viral protein synthesis. IRESs are specialized RNA elements present within the 5’ UTR of mRNAs that recruit ribosomes independently of the 5’ m7G cap structure. hnRNP A1 (heterogeneous nuclear ribonucleoprotein A1), a multifunctional RNA binding protein, is required for the IRES-dependent translation of many specific RNAs within the cell cytoplasm. The phosphorylation of hnRNP A1 is required for its cytoplasmic accumulation. I have identified and validated the role of HK2 in hnRNP A1 cellular localization by immunofluorescence microscopy, by analysis of HRV infection and by siRNA-based screening. These studies show that decreased HK2 protein levels lead to decreased cytoplasmic accumulation of hnRNPA1 during osmotic shock and HRV infection, to a decrease in HRV-infected cells and to decreased caspase activation in osmotically stressed and HRV-infected cells. Thus, HK2 may regulate hnRNP A1 cytoplasmic localization following HRV infection.
Keywords: hnRNP A1; Hexokinase 2; Human Rhinovirus